О pewnym typie intertekstualności w listach apostolskich (na materiale polskich przekładów Listów św. Pawła) - Motyl, Katarzyna (Acta Universitatis Lodziensis. Folia Linguistica, 2005)
The character of the Apostle’s Letters is very complex as apart from the author’s words. There are also quotations from The Old Testament. In my article I would like lo present how those quotations function in Apostle’s Letters o f Paul. I am particularly interested in ways of introducing them and also how they function in the text – they are to deepen and to make understanding of religious content easier. They are also an element which distinquish them from other Letters in the New Testament, forming in that way one of points which influences and have a big impact on the shape of the whole epistolography. This is one of the most important feature of this bible style.